Hadith #2542 - Sunan Abi Dawud - Aqeel bin Shubayb عقيل بن شبيب; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin Sa'id al-Talaqani هشام بن سعيد الطالقاني أبو أحمد البزاز (Sunan Abi Dawud)
Utbah heard the Messenger of Allah (ﷺ) say: Do not cut the forelocks, manes, or tails of horse, for their tails are their means of driving flies, their manes provide them with warmth, and blessing is tide to their forelocks.
Grade: Sahih

Hadith #2543 - Sunan Abi Dawud - Abdul Quddus bin al-Hajjaj al-Khulani عبد القدوس بن الحجاج الخولاني; Aqeel bin Shubayb عقيل بن شبيب; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Muhammad bin Muhajir bin Abi Muslim محمد بن مهاجر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Keep to every dark bay horse with a white blaze and white on the legs, or sorrel with a white blaze and white on the legs , or black with a white blaze and white on the legs.
Grade: Da'if

Hadith #2552 - Sunan Abi Dawud - Aqeel bin Shubayb عقيل بن شبيب; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin Sa'id al-Talaqani هشام بن سعيد الطالقاني أبو أحمد البزاز (Sunan Abi Dawud)
Abu Bashir Al Ansari said that he was with the Apostle of Allaah(ﷺ) on one of his journeys. The Apostle of Allaah(ﷺ)sent a messenger. The narrator ‘Abd Allah bin Abu Bakr said “I think he said while the people were sleeping. No necklace of bowstring or anything else must be left on a Camels’ neck, must be cut off. The narrator Malik said “I think this was due to evil eye.”
Grade: Sahih

Hadith #4948 - Sunan Abi Dawud - Aqeel bin Shubayb عقيل بن شبيب; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin Sa'id al-Talaqani هشام بن سعيد الطالقاني أبو أحمد البزاز (Sunan Abi Dawud)
The Prophet (ﷺ) said: On the Day of Resurrection you will be called by your names and by your father’s names, so give yourselves good names.
Grade: Da'if